Rediscovering the Value of Experience in Education: Through an Investigative Approach to Practices - Zarta Rojas, Fabian Andrey (2025)
The starting point of this article is a reflective exercise guided by the following question: in what ways, and to what extent, is the notion of experience linked to praxis and, consequently, to praxeological research? In this sense, the “constituted space” of experience becomes the raw material of all praxeological inquiry in education. To address this question, five analytical axes are considered: (1) the creative nature of experience; (2) experience as action and memory; (3) experience and action; (4) experience and narration; and (5) experience and research as a way of understanding “in complexity.” The conclusions suggest that praxeological research and reflection in education seek to apprehend lived human experience by integrating a diversity of perspectives.